Audiovisual Translation at the Service of the EU Public Communication 2.0 - Maestri, Alessandro (Journal of Audiovisual Translation, 2021)
Communication is becoming more and more (audio)visual, social and mobile. This is true not only of the entertainment industry but also of commercial advertising and institutional public communication. Consequently, the audiovisual translation industry is flourishing. Although a growing array of products outside the field of entertainment are being localised and/or made accessible, they have received scant attention so far, whether in academic or professional circles. This is notably the case of the institutional video subgenre. This practice report will first address the importance of using increasingly multilingual and multimodal audiovisual products in EU external communication – a tool for reaching out to more citizens on social media and boosting their active participation at a time when populism and Euroscepticism are on the rise. The focus will then shift to the audiovisual communication of the Council of the EU. Through a case study which aims to investigate the internal localisation in all EU official languages of the “#Europeans” series of videos – produced for the 2019 EU elections – the rest of the paper will then outline the main features of the institutional audiovisual translation subgenre. It will also identify some opportunities for improvement: a more integrated and interdisciplinary approach which – together with reinforced collaboration with academia – could lead to a real multilingual creative process right from the initial steps of the audiovisual production process.